The novel long noncoding RNA linc00467 promotes cell survival but is down-regulated by N-Myc. - Bernard Atmadibrata; Pei Y Liu; Nicolas Sokolowski; Lihong Zhang; Matthew Wong; Andrew E Tee; Glenn M Marshall; Tao Liu (PLoS ONE)
The worst subtype of neuroblastoma is caused by MYCN oncogene amplification and N-Myc oncoprotein over-expression. Long noncoding RNAs (lncRNAs) are emerging as critical regulators of gene expression and tumourigenesis. While Myc oncoproteins are well-known to exert tumourigenic effects by regulating the expression of protein-coding genes and microRNAs, little is known about which lncRNAs are Myc targets and whether the Myc target lncRNAs play a role in Myc-induced oncogenesis. Here we performed differential gene expression studies using lncRNA microarray in neuroblastoma cells after transfection with control or N-Myc-specific small interfering RNA (siRNA), and identified N-Myc target lncRNAs including the novel lncRNA linc00467, the expression and function of which were completely unknown. RT-PCR, chromatin immunoprecipitation and luciferase assays showed that N-Myc suppressed linc00467 gene expression through direct binding to the linc00467 gene promoter and reducing linc00467 promoter activity. While N-Myc suppressed the expression of RD3, the protein-coding gene immediately down-stream of linc00467 gene, through direct binding to the RD3 gene promoter and reducing RD3 promoter activity, linc00467 reduced RD3 mRNA expression. Moreover, Affymetrix microarray analysis revealed that one of genes significantly up-regulated by linc00467 siRNA was the tumour suppressor gene DKK1. Importantly, knocking-down linc00467 expression with siRNA in neuroblastoma cells reduced the number of viable cells and increased the percentage of apoptotic cells, and co-transfection with DKK1 siRNA blocked the effects. These findings therefore demonstrate that N-Myc-mediated suppression of linc00467 gene transcription counterintuitively blocks N-Myc-mediated reduction in RD3 mRNA expression, and reduces neuroblastoma cell survival by inducing DKK1 expression.